Analisis Pembingkaian Sosok SBY Dalam Buku Membongkar Gurita Cikeas: Di Balik Skandal Bank Century Karangan George Junus Aditjondro (Studi Analisis Teks Van Dijk) - Riyandari, Defiana Tities (Universitas Semarang, 2013)
The book of Membongkar Gurita Cikeas: Di Balik Skandal Bank Century is George Junus Aditjondro s an activist expression media to critic SBY works on his leadership period. This book contain the social construction in every chapters, texts and languages that written. The framing/construction implementation on this book is using framing analyze. First step is do the Van Dijk text analyze using the elements of tematic, skematic, semantic, sintacist, stilistic and retorist. The text analyze on the book of Membongkar Gurita Cikeas find the constructions on SBY s frame.